2013
DOI: 10.1152/ajplung.00226.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery endothelial cell dysfunction and decreased populations of highly proliferative endothelial cells in experimental congenital diaphragmatic hernia

Abstract: Decreased lung vascular growth and pulmonary hypertension contribute to poor outcomes in congenital diaphragmatic hernia (CDH). Mechanisms that impair angiogenesis in CDH are poorly understood. We hypothesize that decreased vessel growth in CDH is caused by pulmonary artery endothelial cell (PAEC) dysfunction with loss of a highly proliferative population of PAECs (HP-PAEC). PAECs were harvested from near-term fetal sheep that underwent surgical disruption of the diaphragm at 60-70 days gestational age. Highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 44 publications
2
41
0
1
Order By: Relevance
“…With this increase in the expression of NOS3 there has been an increase in the production of nitric oxide, which is the main vasodilator of the cardiovascular system. According to most studies, the expression and the activity of eNOS are reduced in fetuses with CDH, when compared to controls [30][31][32][33]. Then, dexamethasone stimulates the production of NO generating a thinner arteriolar media layer that may decrease pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…With this increase in the expression of NOS3 there has been an increase in the production of nitric oxide, which is the main vasodilator of the cardiovascular system. According to most studies, the expression and the activity of eNOS are reduced in fetuses with CDH, when compared to controls [30][31][32][33]. Then, dexamethasone stimulates the production of NO generating a thinner arteriolar media layer that may decrease pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The C-reactive protein (CRP) level is a well-known risk factor for vascular disease and endothelial dysfunction which are characterized by the decreased production of vasodilators and the increased production of vasoconstriction mediators [14,15,16]. It has been reported that PA EC dysfunction contributes to the development, progression, and severity of CDH-PH in experimental models [17], indicating that endothelial dysfunction-associated proteins may play an important role in the fundamental pathogenesis of CDH.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal pulmonary blood flow and endothelial signaling are known to impair lung growth and alveolarization (32). Pulmonary artery endothelial cells have impaired growth and angiogenic capacity in an experimental model of CDH (33). However, mechanisms that disrupt coordinated growth of the distal lung and vasculature and contribute to prominent IPAV in CDH are not clear.…”
Section: Discussionmentioning
confidence: 99%